Cleaning maintenance of floor finishes in three-star hotels / Muhamad Rosdi Muhamad Ramli - Muhamad Ramli, Muhamad Rosdi (Shah Alam, 2004)
This research will the mainly about the “maintenance of three-star hotel” regarding the cleanliness of floor finishes in main entrance, corridor and lobby area, the aim to this study is to find the problem regarding the all finishes used and cost involved in three-star hotels.All floor finishes has its lifecycle period and with good maintenance the life cycle period of the floor finishes can be longer. The method of the cleaning is very important which need good workers and to use the suitable detergent for taking care of such expensive floor material.The research has gathered the data from a few parties such as housekeeping officer and contractor and later being analysed to identify finding with regarded to the objectives of the research